IMPROVING AUTONOMOUS LEARNING AND LEARNING OUTCOMES OF STUDENT THROUGH GENERATIVE LEARNING ON LINEAR ALGEBRA SUBJECT (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThe real condition on activity learning of linear algebra subject showed that the autonomous learning of students were not optimal yet. It was observed from their activities on learning, such as exploration, elaboration, confirmation and problem solving which they were still doubt and not having the ability. According to the researcher who having experience as the lecturer of linear algebra subject, that conditions were the source of difficulty for students on building their knowledge. Based on that, the researcher tried to develop the new innovation of learning to build the knowledge through the building of impression, the construction of knowledge and generalized it by implementing the model of generative learning. The problem of this study is whether the implementation of generative learning model can improve the autonomous learning and learning outcomes of students. Despitefully, the researcher also observed the quality of learning during the implementation of this learning model. This study was action research with the subject was the students who attended the linear algebra subject on odd semester academic year 2011/2012. The statistic test used Wilcoxon test because the data of this study was not distribution normal. The result showed that the implementation of generative learning model gave the positive impact to the learning quality, autonomous learning and learning outcomes of students on linear algebra subject.Keywords: Generative Learning, Autonomous Learning, Learning Outcomes